Effect of copper salts on hydrothermal oxidative decarboxylation: a study of phenylacetic acid. Issue 18 (6th February 2020) - Fu, Xuan; Jamison, Megan; Jubb, Aaron M.; Liao, Yiju; Aspin, Alexandria; Hayes, Kyle; Glein, Christopher R.; Yang, Ziming
Abstract : Efficient and selective effects of copper salts on hydrothermal oxidative decarboxylation have been discovered and studied. Abstract : Decarboxylation of carboxylic acids is favored under hydrothermal conditions, and can be influenced by dissolved metals. Here, we use phenylacetic acid as a model compound to study its hydrothermal decarboxylation in the presence of copper(ii ) salts but no O2 . Our results showed a strong oxidizing role of copper in facilitating oxidative decarboxylation.